Optimizing The Net Energy of Acetone Production using The Isopropyl Alcohol Dehydrogenation Process - Ihsan, Ahmad Nur; Wibawa, Angga Satria; Ruliyono, Dafiq; Ibrahim, Kevin Maulana; Kindi, Muhammad Alif (Journal of Chemical Engineering Research Progress, 2024)
In order to reduce the dependence on fossil fuels, acetone has emerged as an important platform chemical for various industrial applications. Acetone can be efficiently produced through the dehydrogenation of isopropanol, using metal-based catalysts with high activity and selectivity. The technology for this acetone production was simulated using Aspen HYSYS software, with operating parameters based on the reaction dynamics model for isopropanol dehydrogenation. This study evaluated the modification of the dehydrogenation process to improve energy efficiency by optimizing the heat transfer unit. The product heat leaving the reactor will be cooled in a heat exchanger and the heat is used to increase the heat from the mixer output, this is designed to utilize the process output energy, thus utilizing the heat exchanger as a cooler for the reactor output, thereby reducing additional energy consumption and improving the overall process sustainability. The modification includes increasing the acetone production yield and energy efficiency in the heat transfer unit to reduce energy consumption from 10.9296 MMBtu/h to 7.7431 MMBtu/h by utilizing the heat exchanger as a cooler for the reactor output back and at the same time a heater for the mixer output as a process optimization. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).